Assessment of Menstrual Waste Disposal and the Environment: The Role of Adult Education in Nigeria - Olatumile, Adekunle; Ajayi, Elizabeth Aanuoluwapo (American International Journal of Social Science Research, 2019)
The phenomenon of menstruation portends great impact on the environment and its calls for concern. Environmental effect of menstrual hygiene and related issues has been downplayed Nigeria. This study was conducted to assess menstrual waste disposal practices and it’s implication on the environment. A self-constructed questionnaire was used to elicit information for the survey design research. While multistage sampling technique was used to select 194 participants of females within the age range of 20 and 59 in Akungba-Akoko, Ondo State. The four research questions raised for the study were answered descriptively while the two hypotheses were tested using inferential statistics at 0.05 level of significance. Finding revealed among others that though the female adults were aware of the environmental implication of indiscriminate menstrual waste disposal, they practices does not correlate with their awareness because menstrual waste disposal knowledge is not in public domain, while the knowledge gained is informal from older women who themselves lack adequate knowledge. It was therefore recommended among others, that adults deserves to be empowerment by Adult Education through Menstrual Waste Education (MWE)   to improve hygiene as well as the environment during menstrual cycle due to the precarious situation it places on women.